Microsatellite Instability in Endometrial Carcinoma. - Toor, Sharanjit Singh; Kinra, Prateek; Kumar, Aman; Hothi, Onkar Singh (Annals of Pathology and Laboratory Medicine, 2020)
Background: Endometrial carcinoma is the commonest gynaecological malignancy in the western countries with a standardised incidence of 8 per 100000 women. In India and Southeast Asia, the incidence of endometrial carcinoma is low but it is increasing due to increasing prevalence of obesity, diabetes, early menarche, late menopause, late marriage and declining birth rate. The study aimed to identify the role of microsatellite instability in endometrial carcinoma. Although MSI has been studied extensively in colorectal carcinoma there have been very few studies in southeast asian region regarding association of MSI and prognosis in endometrial carcinoma. To the best of our knowledge this is first study in India. Method: A Descriptive study in which 40 patients of endometrial carcinoma were studied. MSI was detected using immunohistochemistry (MSH-1, PMS-2, MSH-2, MSH-6). Statistical Analysis was done using SPSS software and fisher exact test was used to calculate p value. p value less than.05% was considered significant. Results: Overall prevalence of microsatellite instability was 40%. Microsatellite instability was associated with higher tumor grade, myometrial invasion>50% and presented in initial stages compared to microsatellite stable tumors. Conclusion: Our study showed statistically significant association between microsatellite instability and Figo staging, tumor grade and myometrial invasion.